Safety and effectiveness of BNT162b2 mRNA Covid-19 vaccine in adolescents. Issue 5 (31st January 2022) - June Choe, Young; Yi, Seonju; Hwang, Insob; Kim, Jia; Park, Young-Joon; Cho, Eunhee; Jo, Myoungyoun; Lee, Hyunju; Hwa Choi, Eun
Abstract: In South Korea, all 12th grade students (highs school seniors) were offered BNT162b2 vaccine starting July 19, 2021; while 10 th –11th grade students were not eligible. We conducted a nationwide retrospective cohort study by to determine the safety and effectiveness of BNT162b2 mRNA Covid-19 vaccine in adolescents against SARS-CoV-2 infection. Among 444, 313 persons who received the first dose of vaccine, reporting rate for myocarditis and/or pericarditis was 1.8 per 100, 000 (95% C.I. 0.8–3.5) among first-dose recipients and 4.3 per 100, 000 (95% C.I. 2.6–6.7) in second-dose recipients. Vaccine effectiveness against symptomatic/asymptomatic SARS-CoV-2 infection 14 days post-first dose vaccination was 91.1% (95% C.I. 89.6–92.5), and 14 days post-second dose was 99.1% (95% C.I. 98.5–99.5). In this retrospective cohort study, BNT162b2 vaccination was safe and was associated with a significantly lower risk of SARS-CoV-2 infection, suggesting that vaccination in adolescent may reduce the burden of Covid-19.